KORELASI ANTARA PENGETAHUAN DENGAN SIKAP ILMIAH PENCEGAHAN KEBAKARAN LAHAN DAN HUTAN PADA PESERTA DIDIK DI MTsN BUKIT BATU KABUPATEN BENGKALIS, RIAU - Handayani, Oshi; ', Yustina; ', Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the correlation between knowledge and scientific attitude land and forest fire prevention STUDENTS in MTsN Bukit Batu Bengkalis, Riau that was conducted in November 2015 to May 2016. The sample in this study were 63 students randomly selected in VIII grade in school year 2015/2016 and two science teachers as supporting data. The parameters of this study is the knowledge of the land and forest fire prevention and scientific attitude land and forest fire prevention. Instrument knowledge with written tests, scientific attitude is measured by using a closed questionnaire that has been valid and reliable and interview guidelines. The collected data were analyzed by descriptive and inferential statistics simple regression test. The results of data analysis showed that there is a low correlation between knowledge with scientific attitude land and forest fire prevention learners in MTsN Bukit Batu Bengkalis, Riau.Keywords: Knowledge, Scientific Attitude, Land and Forest Fires